Effects of longitudinal vibration on the mechanical properties of mild steel weldments - Tewari S.P.; Shanker A. (My University, 2025)
This paper deals with the effect of longitudinal vibration on the mechanical properties of mild steel weldments. The weldments were prepared under different frequencies and amplitudes of vibration. Experiment was carried out in the frequency and amplitude ranges of 0-400 Hz and 0-40 μm respectively. It is found that yield strength, ultimate tensile strength and hardness improves for mild steel specimens welded under vibratory conditions. It is further observed that this improvement in the mechanical properties is appreciable up to 30 μm amplitude. © 1993, Institution of Mechanical Engineers. All rights reserved.